Child labour prevalence in Ghana - DJALALOVA, Malika (KDI School, 2015)
This thesis attempts to contextualize the practive of child labour in Ghana by looking into various determinants, as well as examining how well the Ghanian government was able to achieve the targeted goal to alleviate child labour and integrate children to primary school. It looks covers the legal frameworks that have been developed to give child rights and protect them for hazardous working conditions, or work overall. The study is done mostly with the help of the GLSS 6, and findings and analysis are based on the observation made from the survey results.
Thesis(Master) --KDI School:Master of Development Policy,2015